Comparison of validation protocols for blood pressure measuring devices in children and adolescents - Stabouli, Stella; Chainoglou, Athanasia; Evripidou, Kleo; Simão, Carla; Antza, Christina; Petrou, Panagiotis; Hamdani, Gilad; Calpe, Javier; Lurbe, Empar (Frontiers in Cardiovascular Medicine, 2022)
Accuracy of blood pressure (BP) measurement is important for the evaluation of hypertension in children and adolescents, and it is critically dependent upon the accuracy of the BP measuring device. A device that could pass validated protocols with reliable accuracy would be desirable in clinical and research settings. Several scientific organizations have published recommendations on the validation of different BP measuring devices. Most of them focus on adults but separate recommendations and validation criteria for BP devices intended for use in children and adolescents are included in some validation protocols. In this review, we compare the validation criteria for BP measuring devices among consensus documents from different scientific organizations focusing on the pediatric population and we discuss the evidence gaps targeting the needs for validated BP measuring devices in children and adolescents. We also highlight common pitfalls in the validation studies of BP measuring devices in children and adolescents using the example of office BP devices.